2008
DOI: 10.1111/j.1365-2966.2008.13599.x
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of accretion flow with a toroidal magnetic field

Abstract: In this paper, we investigate the time evolution of quasi-spherical polytropic accretion flow with a toroidal magnetic field. We focus in particular on the astrophysically important case in which the adiabatic exponent γ = 5/3. In this scenario, we have assumed that the angular momentum transport is a result of viscous turbulence and we have used the α-prescription for the kinematic coefficient of viscosity. The equations of accretion flow are solved in a simplified one-dimensional model that neglects the lati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…Also, these relations show p 0 (t) and b 0 (t) are dependent on the behaviour of ρ 0 (t). Our results are in agreement with the previous findings for such time-dependent systems (Ogilvie 1999;Khesali & Faghei 2008, 2009. Moreover, self-similar solutions indicate that electrical conductivity is scaled with time as t −1/3 .…”
Section: Discussionsupporting
confidence: 93%
“…Also, these relations show p 0 (t) and b 0 (t) are dependent on the behaviour of ρ 0 (t). Our results are in agreement with the previous findings for such time-dependent systems (Ogilvie 1999;Khesali & Faghei 2008, 2009. Moreover, self-similar solutions indicate that electrical conductivity is scaled with time as t −1/3 .…”
Section: Discussionsupporting
confidence: 93%
“…Because we apply a steady self‐similar method to solve the system equation, Π is constant throughout the disc. In fact, Π is a function of position and time (Machida, Nakamura & Matsumoto 2006; Oda et al 2007; Khesali & Faghei 2008, 2009). Studies of hot accretion flows have found that the typical value of Π is in the range 0.01–1 (De Villiers, Hawley & Krolik 2003; Beckwith, Hawley & Krolik 2008).…”
Section: Basic Equationsmentioning
confidence: 99%
“…Thus, we introduce a similarity variable ξ and assume that each physical quantity is given by the following form: where is a constant and its value can be obtained from typical values of the system. In addition, we assumed that under similarity transformations is a function of ξ only (Khesali & Faghei 2008, 2009). Substitution of the above transformations into the basic equations ()– (4) yields the dimensionless equations below: These equations provide a fourth‐order system of non‐linear ordinary differential equations that must be solved numerically.…”
Section: Self‐similar Solutionsmentioning
confidence: 99%